2001
DOI: 10.1006/mthe.2001.0312
|View full text |Cite
|
Sign up to set email alerts
|

A Regulated, NFκB-Assisted Import of Plasmid DNA into Mammalian Cell Nuclei

Abstract: The success of synthetic DNA delivery systems in human gene therapy will be enhanced by increasing transfection efficiencies and by providing tighter control over targeting of the DNA into the nucleus. Here, we used DNA vectors that contain repetitive binding sites for the inducible transcription factor NFkappaB, which is transported into the nucleus by the nuclear import machinery. Nuclear entry of the modified vectors was augmented 12-fold and was associated with corresponding increase in gene expression. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 30 publications
3
85
0
Order By: Relevance
“…This can be a cell-specific vector, whose specificity is at the level of the nuclear import of the plasmid DNA. Mesika et al (2001) have used DNA vectors that contain repetitive binding sites for the inducible transcription factor NFjB, which is transported into the nucleus by the nuclear import machinery. Nuclear entry of the modified vectors was augmented 12-fold and was associated with a corresponding increase in gene expression.…”
Section: Transcription Factorsmentioning
confidence: 99%
“…This can be a cell-specific vector, whose specificity is at the level of the nuclear import of the plasmid DNA. Mesika et al (2001) have used DNA vectors that contain repetitive binding sites for the inducible transcription factor NFjB, which is transported into the nucleus by the nuclear import machinery. Nuclear entry of the modified vectors was augmented 12-fold and was associated with a corresponding increase in gene expression.…”
Section: Transcription Factorsmentioning
confidence: 99%
“…We, and others, have subsequently shown that nuclear import of plasmid DNA is sequence dependent, requires karyopherins (importins) and the small GTPase RAN, and occurs through the nuclear pore complex (NPC). [14][15][16][17][18] In our model of plasmid nuclear import, we propose that transcription factors present in the cytoplasm bind to the DTS and coat the plasmid with nuclear localization sequences (NLSs) that utilize importins to cross the NPC, which regulates the nucleocytoplasmic shuttling of macromolecules during interphase. [19][20][21] We have also developed a tissue-specific DTS, utilizing the smooth muscle g-actin (SMGA) promoter, that mediates nuclear import of pDNA specifically in smooth muscle cells (SMCs).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in cultured and permeabilized cells from our laboratory and others support this model. 3,14,15,23,24 Unlike the SV40 enhancer, many other strong viral promoters such as the CMV iep or the RSV LTR appear not to mediate nuclear import even though they bind many of the same transcription factors as the SV40 sequence. 3,15 The likely reason for this is that it is the overall organization and structure of the transcription factor-DNA complex that is important and that more than one specific transcription factor is needed for nuclear localization.…”
mentioning
confidence: 99%